2021
DOI: 10.1108/sbr-07-2021-0102
|View full text |Cite
|
Sign up to set email alerts
|

Ethics and accounting education: does teaching stand-alone religious courses affect accounting students’ ethical decisions?

Abstract: Purpose Undergraduate accounting program at Umm Al-Qura University in Saudi Arabia is a unique case. The program includes 147 credit hours of which 28 credit hours are religious courses. This study aims to examine the effect of teaching these religious courses on students’ ethical perceptions and decisions. Design/methodology/approach A survey was conducted for a sample of accounting students at Umm Al-Qura University. The sample was divided into two groups; the first group includes students who did not stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…al., 2020). This assertion is supported by Ebaid (2022), who found that teaching religious courses improved students' perceptions of business ethics and enhanced their ethical decision-making. Moreover, religion strongly influences an individual's attitudes, behaviors, and decisions (Khalil & Sidani, 2020), with higher levels of religiosity among students correlating with increased ethical perceptions regarding tax avoidance (Dewanta & Machmuddah, 2019).…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…al., 2020). This assertion is supported by Ebaid (2022), who found that teaching religious courses improved students' perceptions of business ethics and enhanced their ethical decision-making. Moreover, religion strongly influences an individual's attitudes, behaviors, and decisions (Khalil & Sidani, 2020), with higher levels of religiosity among students correlating with increased ethical perceptions regarding tax avoidance (Dewanta & Machmuddah, 2019).…”
Section: Discussionmentioning
confidence: 85%
“…Ethics are crucial in enhancing the profession's image and societal development. One profession highly reliant on professional image assessment during practice is accounting (Ebaid, 2022). The criteria proposed by Sugiyono (2019) were utilized to determine the sample size: 1) Research samples ranged from 30 to 500 participants; 2) If samples were categorized (Male and Female, Married and Unmarried), each category comprised twenty samples; 3) If multivariate analysis was employed, the sample size should be ten times the number of variables in the study; 4) Basic experiments with control and experimental groups ideally consisted of sample sizes ranging from 10 to 20.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A university education shapes part of the personality of an accountant. Universities are responsible for creating accountants with the skills and competencies needed to practice the accounting profession and equipping accounting students who become future accountants with the courage and values of honesty and ethics (Ebaid, 2022). As a result, students should participate in an ethics intervention before finishing their accounting course, as this will help them to better prepare for dealing with whistleblowing circumstances they might run into as future accountants and the need to overcome them and familiarize them with the ethical principles, goals, and mission of the accounting profession in society (Namazi et al, 2023).…”
Section: Introductionmentioning
confidence: 99%